EL ARCHIPIÉLAGO DEL PERRO - Philippe Claudel - Cafasso Maberino, Patricia (EQUINOCCIO, 2021)
Título: El archipiélago del perro Autor: Phillipe Claudel Año: 2019 Editorial: Salamandra Ciudad: Barcelona Páginas: 205